Placental dysfunction in uncomplicated and complicated intrauterine growth restriction by preeclampsia and neonatal outcome. (12th December 2022) - Tagliaferri, Salvatore; Travaglino, Antonio; Raffone, Antonio; Saccone, Gabriele; Campanino, Maria Raffaela; Zara, Giuseppe; Ammendola, Alessandra; Pini, Nicolò; Maruotti, Giuseppe Maria; Magenes, Giovanni; Signorini, Maria Gabriella; Guida, Maurizio; et al.
Abstract: Objectives: To investigate the use of computerized cardiotocography (cCTG) parameters in Intrauterine Growth Restriction (IUGR) pregnancies for the prediction of 1) complication with preeclampsia; 2) placental histological abnormalities, and 3) neonatal outcomes.  Study design: A single-center observational retrospective case-control study was performed by reviewing medical records, cCTG databases and pathological reports of women with singleton pregnancy and IUGR uncomplicated (controls) and complicated by preeclampsia (cases). Primary endpoint was the association between cCTG parameters and preeclampsia in IUGR. Secondary endpoints were the association between cCTG parameters and 1) placental abnormalities, and 2) neonatal outcomes. The one-way ANOVA test was used to compare cCTG parameters in cases and controls. t -test was applied to compare neonatal outcomes and placental abnormalities in both groups. The Spearman Test value Correlation coefficients between the cCTG parameters and neonatal outcome in the two groups. A p value < .05 was considered significant for all analyses. Results: Among all cCTG parameters, a significant association with preeclampsia in IUGR was found for Fetal Heart Rate (FHR, p  = .008), Delta ( p  = .018), Short Term Variability (STV, p  = .021), Long Term Variability (LTV, p  = .028), Acceleration Phase Rectified Slope (APRS, p  = .018) and Deceleration Phase Rectified Slope (DPRS, p  = .038). Of all placental histologic abnormalities, only vascular alterations at least moderate were significantly associated with increased FHR ( p  = .02). About neonatal outcomes, all cCTG parameters were significantly associated with birth weight, Apgar index at 1 and 5 min, pH and pCO2. FHR, LTI, Delta, Approximate Entropy (ApEn) and LF were significantly associated with pO2 ; LTI, Interval Index (II) and ApEn with base excess. Among controls, Delta, ApEn, Low Frequency (LF) and High Frequency (HF) were significantly associated with pCO2, while among cases, STV and Delta were significantly associated with pH; STV, LTI, Delta, ApEn, LF and HF with pCO2 ; STV, LTI, Delta and ApEn with pO2 ; HF with base excess; FHR and LF with lactates. Conclusions: cCTG parameters may be useful to detect complication with preeclampsia in IUGR pregnancies. Regarding placental status, cCTG parameters may detect overall circulation alterations, but not specific histological abnormalities. Lastly, all cCTG parameters may predict neonatal outcomes, helping to tailor the patients' management.